Comparison of the Efficacy of Anatomic and Non-anatomic Hepatectomy for Hepatic Alveolar Echinococcosis: Clinical Experience of 240 Cases in a Single Center - A, Jide; Zhang, Jingni; Chai, Jinping; Zhao, Shunyun; Wang, Hao; A, Xiangren; Yang, Jinyu (Frontiers in Public Health, 2022)
Background Hepatic alveolar echinococcosis (AE) is a zoonotic parasitic disease. There are more than 16,000 new cases each year, approximately 60 million people are threatened, and the annual direct economic loss is RMB 3 billion. The prevalence of AE in some areas of the Qinghai–Tibet Plateau is as high as 6.0%. Radical resection, including anatomic and non-anatomic hepatectomy, for advanced AE can significantly prolong the survival time of patients. However, there is no literature compared the efficacy of anatomic and non-anatomic hepatectomy. Therefore, by comparing various clinical evaluation indices between anatomic and non-anatomic hepatectomy, this study explored the short-term and long-term efficacy of these two surgical methods for AE. Methods The clinical data of patients with AE who underwent radical hepatectomy at Qinghai Provincial People's Hospital from January 2015 to January 2021 were retrospectively analyzed. The patients were divided into two groups by surgical method, that were, non-anatomic hepatectomy group and anatomic hepatectomy group. We compared these two groups focusing on basic preoperative data, such as age, sex, lesion size, and liver function parameters; main intraoperative evaluation indices, such as operation time, intraoperative porta hepatis occlusion time, intraoperative blood loss, and blood transfusion; and postoperative recovery evaluation indicators, such as postoperative liver function, incidence of surgical complications, and AE recurrence. Results A total of 240 patients were enrolled in this study, including 123 in anatomic hepatectomy group and 117 in non-anatomic hepatectomy group. There were no significant differences (P > 0.05) between baseline characteristics. Anatomic hepatectomy group was advantageous than non-anatomic hepatectomy group regarding intraoperative blood loss (P < 0.001), blood transfusion (P < 0.001), and porta hepatis occlusion time (P < 0.001). There were statistically significant differences in postoperative liver function (aspartate aminotransferase: P < 0.001; alanine aminotransferase: P < 0.001), surgical complications (P < 0.001), and AE recurrence rate (P = 0.003). The median survival of patients in the anatomic hepatectomy group was 66 months, compared to 65 months in the non-anatomic hepatectomy group (χ2 = 4.662, P = 0.031). Conclusions Anatomic hepatectomy was not only safe for AE but also showed better short-term and long-term superiority than non-anatomic hepatectomy.